The Impact of Special Exercises Using (Jump Trainer) to Develop some of the Physical Abilities of the Completion of the 100m - Noori Taresh, Hasan; Sabah Falih, Louai; Azad Saleh, Newin (International Journal of Psychosocial Rehabilitation, 2020)
The high level of achievement and sports record during sessions of the Arab and Asian Olympics year after year, a large number of researchers interest in the study of training means and search for the best means of increasing the effectiveness of the trainee to create a renewal in training, from the interest of the researcher in this effectiveness being a coach in the events speed found low use of modern training means (Trainer Jump) including resistance exercises muscles working class youngsters effectiveness (100m), which is the problem, no doubt, as well as the need for diversification in the training means an incentive or motive to raise achievement in this category and the researcher uses (Jump Trainer) as a means of new training courses in raising the efficiency of sports obese runners (100m) and serve those sports events especially short running for giving new results. The use of the (Jump Trainer) was an effective influence in the development of some of the physical abilities through the application of special exercises, which were affected in the development of the special force and speed, which led to the development of achievement in a positive manner and must be the focus in the selection of appropriate exercises, according to modern training methods for all events speed.